Pengaruh Price To Book Value, Earning Per Share Dan Debt To Equity Rasio terhadap Harga Saham Bank Umum Swasta Nasional - SOCHIB, SOCHIB (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
The stock price is a reference for many in the Indonesia Stock Exchange (IDX), especially investors and prospective investors who have expectations of stock prices at the end of the closing day of the Stock Exchange. Investors depend on the stock price on the exchange because this is part of the welfare when investors are willing to release their funds to the stock exchange. The company's management also has an obligation to inform its performance during a certain period of time. The company's management performance will be reflected in the stock price at the close of the stock exchange. There are several factors that can affect management performance and stock prices, such as PBV, EPS, and DER. Because this factor will fundamentally give impetus to the occurrence of stock prices on the exchange. Management is very interested in indicators such as PBV, EPS, and DER, it can be seen the level of profits obtained by the company, the ability of the company to utilize the assets it owns. This study aims to empirically examine the effect of PBV, EPS, and DER on the share price of National Private Commercial Banks. The researcher used 20 samples of the national private banking sector listed on the Indonesian Stock Exchange for the 2014-2016 period to obtain 60 observations. The hypothesis is tested using regression analysis which can be used to predict the condition of the next few years after knowing the magnitude of the effect of the independent variables. The results obtained in this study that PBV, EPS and DER affect stock prices. It is expected that the results of this study can contribute to the development of Financial Management Sciences in Indonesia.